The Psychopathological Influence of Congenital Heart Disease in Korean Male Adolescents: An Analysis of Multiphasic Personal Inventory Test Results - Oh, Chang Hyun (Yonsei University College of Medicine, 2012)
PURPOSE: The aim of this study was to evaluate the psychopathological influence of congenital heart disease (CHD) in Korean 19-year-old males. MATERIALS AND METHODS: The authors compared the Korean military multiphasic personal inventory (KMPI) military profiles of 211 CHD cases (atrial septal defect, ventricular septal defect, patent ductus arteriosus, or combined CHD) with the KMPI profiles of 300 normal controls. The CHD group was also divided according to whether or not the subjects had undergone open cardiac surgery in order to evaluate the psychopathological effects of an operation among the subjects. RESULTS: A decreased result on the faking-good response scale and an increased result on the faking-bad response were observed in the CHD group compared to the control (p<0.01). The neurosis scale results, including anxiety, depression and somatization symptoms, were markedly increased in the CHD group compared to the control (p<0.01). The severity level of personality disorder was also increased in the CHD group (p<0.001). Differences in KMPI scale scores were not related to open cardiac surgery history. CONCLUSION: In this study, young males with CHD tended to report more abnormal results on the multiphasic personal inventory test in comparison to normal subjects, suggesting that CHD may be related to psychopathology in young males in Korea. Therefore, clinicians are recommended to evaluate the psychopathological traits of patients with CHD.